Preparation and application of Anderson type polyacid modified Co-MOF nano flower-shaped electrocatalyst

Co-MOF is modified by Anderson-type polyacid NiMo6 to form Co-MOF/NiMo6 composite material, which solves the problem of polyacids being easily soluble in water and poor conductivity of metal-organic frames, and improves the efficiency of ammonia production by electrocatalytic nitrate reduction.

CN119877028AActive Publication Date: 2025-04-25HARBIN UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510096716.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Polyacids are easily soluble in water and have poor conductivity of metal-organic frameworks, which limits the electrocatalytic efficiency of synthesized ammonia catalytic materials with electrocatalytic nitrate reduction.

Method used

Co-MOF is modified by Anderson-type polyacid NiMo6 to form a Co-MOF/NiMo6 composite material, and the Co-MOF surface is etched with strong acidity of NiMo6 to form a nanoflower-like structure, increasing the specific surface area and improving electron transport capability.

Benefits of technology

The efficiency of electrocatalytic nitrate reduction in ammonia is improved, the charge separation ability and electrical response rate of the catalyst are enhanced, and the problem of easy dissolution of polyacids is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005253053810000011
    Figure HDA0005253053810000011
  • Figure HDA0005253053810000012
    Figure HDA0005253053810000012
  • Figure HDA0005253053810000021
    Figure HDA0005253053810000021
Patent Text Reader

Abstract

The invention relates to preparation and application of an Anderson type polyacid modified Co-MOF (Metal Organic Framework) nano flower-shaped electrocatalyst. The invention aims to solve the problems that the existing polyacid-based material is poor in electro-catalysis capability and easy to dissolve due to polyacid enrichment and the metal organic framework is poor in conductivity as a substrate material, and the like, and the electro-catalysis efficiency of the ammonia production material is improved. The invention designs and develops a cobalt-based metal-organic framework (Co-MOF for short) nano flower-shaped electrocatalyst (Co-MOF / NiMo6 for short) modified by Anderson type nickel molybdenum polyacid (NiMo6 for short), the cobalt-based metal-organic framework (Co-MOF / NiMo6 for short) nano flower-shaped electrocatalyst plays an etching role based on the strong acidity of polyacid, and the composite material has a nano flower-shaped structure. The Anderson type polyacid modified Co-MOF nano flower-shaped electrocatalyst not only has a layered structure with a high specific surface area and abundant active sites, but also solves the problem that polyacid is easily dissolved in water. The Co-MOF / NiMo6 composite electro-catalytic material obtained by the invention is used for producing ammonia by electro-catalyzing nitrate radical reduction at normal temperature and normal pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst materials for electrocatalytic nitrate reduction to synthesize ammonia, and specifically relates to the preparation and application of an Anderson-type polyacid-modified Co-MOF nanoflower-shaped electrocatalyst. Background Art

[0002] Due to the large-scale discharge of domestic sewage and industrial wastewater and the extensive use of agricultural fertilizers, nitrates are increasingly accumulating in natural water bodies and have become an important pollutant that harms water resources. Therefore, taking effective measures to remove nitrates from water bodies is a top priority for water pollution control. The electrocatalytic nitrate reduction method for ammonia production can not only effectively remove the pollutant nitrate from water bodies, but also produce high-quality and high-value zero-carbon hydrogen-rich fuel ammonia, which improves environmental pollution while alleviating the energy crisis and has important application prospects. In order to improve the yield and efficiency of synthetic ammonia, it is necessary to rationally design the catalyst for the electrocatalytic reduction of nitrate ions, which is the technical breakthrough point of this research direction.

[0003] Polyoxometalates (POMs), also known as polyacids, are nano-sized electron-rich inorganic metal oxygen-containing clusters composed of pre-transition metals (Mo, W, V, Nb, Ta) coordinated with oxygen atoms. Polyacids have rich structures and diverse compositions. By changing the types of heteroatoms, their composition, structure and charge density can be adjusted. Among them, Anderson-type polyacids have strong redox ability and are suitable for electrocatalytic reactions. However, polyacids are highly soluble in water and organic solvents, and their stability as electrode materials is poor, which limits their further application. Metal-organic framework materials, also known as MOFs, are a type of porous crystalline materials composed of metal nodes and organic connectors. They have unique advantages, such as adjustable composition and ratio of metal sites, high porosity, large surface area, which is conducive to the adsorption of catalytic reaction precursors, and can form polyacid-based metal-organic framework materials through electrostatic adsorption, direct bonding or encapsulation with polyacids, and improve electrocatalytic performance through the synergistic effect of the two.

[0004] This patent designs and develops a cobalt-based metal-organic framework (Co-MOF) nanoflower-shaped electrocatalyst (abbreviated as Co-MOF / NiMo6) modified by an Anderson-type nickel-molybdenum polyacid (abbreviated as NiMo6). Based on the strong acidity of the polyacid, it plays an etching role. The anions of the synthesized NiMo6 partially replace the 2-MeIM anions on the surface of Co-MOF, and lead to the reconstruction of the skeleton. Under the synergistic effect of PVP, Co-MOF / NiMo6 is finally formed. The composite material has a nanoflower-shaped structure. This Anderson-type polyacid-modified Co-MOF nanoflower-shaped electrocatalyst not only has a layered structure with a high specific surface area and abundant active sites, but also solves the problem that the polyacid is easily soluble in water. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of easy enrichment and dissolution of polyacids and poor conductivity of metal-organic frameworks, and to improve the electrocatalytic efficiency of catalytic materials for electrocatalytic nitrate reduction to synthesize ammonia.

[0006] 1. Preparation of NiMo6 polyacid: (NH 4)6 7O 24 ·4H2O (5-8g) is dissolved in 80mL of deionized water to obtain a solution and heated to boiling. Dissolve NiSO4·5H2O (0.6-1g) in 20mL of deionized water and pour into the above boiling solution. In order to obtain purer crystals, the solution is recrystallized. The mixed solution is allowed to stand and cool. During the cooling process, NiMo6 crystals will gradually crystallize out of the solution. After the crystallization process is basically completed, use a Buchner funnel with a suction filtration bottle to separate the crystals from the mother liquor by suction filtration to finally obtain light blue crystals.

[0007] 2. Preparation of metal organic framework Co-MOF: Dissolve Co(NO3)2·6H2O (0.3-0.4g) in 100mL deionized methanol, and dissolve 2-methylimidazole (0.3-0.4g) in 100mL deionized methanol. Then mix the above solutions, first put the mixed solution into an ultrasonic cleaner for 20 minutes, then stir for 30 minutes, and let it stand for 24 hours. Collect the purple product by centrifugation, then wash with deionized methanol, and vacuum dry at 60°C for 12-14 hours to obtain Co-MOF.

[0008] 3. Preparation of composite materials: Dissolve Co-MOF (0.2-0.5 g) in 170 mL of deionized methanol, dissolve NiMo6 (0.2-0.5 g) in 70 mL of deionized water, mix the solutions, then add polyvinyl pyrrolidone (0.01-0.05 g), stir the mixture for 8 hours, and then let it stand for 24 hours. Collect the product by centrifugation, then wash it with methanol and water 2-3 times, respectively, and vacuum dry it at 60 ° C for 12-14 hours to obtain Co-MOF / NiMo6.

[0009] The temperature range of the cooling described in step 1 is 22 to 25°C.

[0010] The volume of deionized methanol described in step 2 is 100 mL.

[0011] The masses of Co(NO3)2·6H2O and 2-methylimidazole described in step 2 are 3-4g and 4-5g.

[0012] The mass of polyvinyl pyrrolidone (PVP) described in step 3 is 0.01-0.05g.

[0013] The drying temperature in step 2 and step 3 is 60° C., and the drying time is 720-840 minutes.

[0014] The drying process described in step 3 should be performed under vacuum conditions.

[0015] Compared with the prior art, the present invention has the following characteristics:

[0016] 1. The present invention is the first to prepare a Co-MOF / NiMo6 composite electrocatalyst by static synthesis. The Co-MOF / NiMo6 composite electrocatalyst is rose-shaped. The flower-like structure formed by the staggered nanosheets increases the specific surface area of ​​the material. The composite of Co-MOF and Anderson-type polyacid enhances the electron transmission ability of the catalyst and improves the electrical response rate. NiMo6 polyacid is uniformly attached to the surface of the Co-MOF sheet, which increases the specific surface area of ​​the composite material, promotes the charge separation of the composite material, and improves the electrocatalytic ability.

[0017] Second, the present invention uses in-situ synthesis to make NiMo6 polyacid uniformly dispersed and stably attached to the surface of Co-MOF. This solves the problem that NiMo6 polyacid is easy to dissolve and agglomerate during the catalytic reaction. The present invention is the first example of Co-MOF / NiMo6 polyacid composite electrocatalytic material applied to electrocatalytic nitrate reduction to produce ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope image of Co-MOF material.

[0019] Figure 2 This is a scanning electron microscope image of Co-MOF / NiMo6 material.

[0020] Figure 3 This is a transmission electron microscopy image of Co-MOF / NiMo6 composite material.

[0021] Figure 4 Infrared spectra of Co-MOF, NiMo6 and Co-MOF / NiMo6 composites.

[0022] Figure 5 These are the XRD diagrams of Co-MOF, NiMo6 and Co-MOF / NiMo6 composites.

[0023] Figure 6 This is the ammonia production rate diagram and Faraday efficiency diagram of Co-MOF / NiMo6 composite material in neutral electrolyte (0.1mol / LNaNO3 and 0.1mol / L Na2SO4) at room temperature and pressure, at a voltage of -0.5 to -0.9V for 1 hour.

[0024] Figure 7 This is the electrochemical linear sweep voltammogram of Co-MOF / NiMo6 composite material in the presence or absence of nitrate. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0026] Implementation Case 1

[0027] This embodiment is a Co-MOF / NiMo6 nanoflower catalyst, which is prepared according to the following method:

[0028] (1) Preparation of NiMo6 polyacid: (NH4)6Mo7O 24 ·4H2O (5-8g) is dissolved in 80mL of deionized water to obtain a solution and heated to boiling. Dissolve NiSO4·5H2O (0.6-1g) in 20mL of deionized water and pour into the above boiling solution. In order to obtain purer crystals, the solution is recrystallized. The mixed solution is allowed to stand and cool. During the cooling process, NiMo6 crystals will gradually crystallize out of the solution. After the crystallization process is basically completed, use a Buchner funnel with a suction filtration bottle to separate the crystals from the mother liquor by suction filtration to finally obtain light blue crystals.

[0029] (2) Preparation of Co-MOF: Dissolve Co(NO3)2·6H2O (3-4 g) in 100 mL of deionized methanol and dissolve 2-methylimidazole (4-5 g) in 100 mL of deionized methanol. Then mix the above solutions, put the mixed solution into an ultrasonic cleaner for 20 minutes, stir it for 30 minutes, and let it stand for 24 hours. Collect the purple product by centrifugation, wash it with deionized methanol, and vacuum dry it at 60°C for 12-14 hours to obtain Co-MOF.

[0030] (3) Preparation of Co-MOF / NiMo6 composite material: Co-MOF (0.3-0.4 g) was dissolved in 170 mL of deionized methanol, and NiMo6 (0.3-0.4 g) was dissolved in 70 mL of deionized water. The solutions were mixed, and then polyvinyl pyrrolidone (0.012 g) was added. The mixture was stirred for 8 hours and then allowed to stand for 24 hours. The product was collected by centrifugation, and then washed with methanol and water 2-3 times, respectively, and dried under vacuum at 60°C for 12 hours to obtain Co-MOF / NiMo6.

[0031] Comparative Case 1

[0032] This comparative case provides a Co-MOF electrocatalyst, which is different from implementation case 1 in that NiMo6 is not added after the solution is mixed in step (3).

[0033] Comparative Case 2

[0034] This comparative case provides a NiMo6 electrocatalyst, which is different from implementation case 1 in that Co-MOF is not added after the solution is mixed in step (3).

[0035] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0036] Figure 1 Shown is a scanning electron microscope image of the Co-MOF material, showing that the Co-MOF material is micron-sized and has multiple three-dimensional cubic block structures.

[0037] Figure 2 Shown is a scanning electron microscope image of Co-MOF / NiMo6 material, and it is observed that the prepared Co-MOF / NiMo6 exhibits a rose-like structure with an average size of 2 μm.

[0038] Figure 3 The following is a transmission electron micrograph of the Co-MOF / NiMo6 composite material. It was observed that polyacid particles were evenly distributed on the surface of the Co-MOF layered structure, indicating that NiMo6 was evenly distributed on the surface of the nanosheets.

[0039] Figure 4The infrared spectra of Co-MOF, NiMo6 and Co-MOF / NiMo6 composite materials are shown in the figure. As shown in the figure, the nanomaterials have a wavelength of 400-1400 cm -1 There are infrared characteristic peaks in the range of 425, 1175 and 1339 cm -1 There are three absorption peaks at 650, 900 and 950 cm, which are attributed to the stretching vibrations of Co-N, CN and C=N in the Co-MOF structure. -1 The absorption peaks at are attributed to the Mo-O-Mo, Mo-O and Ni-O vibrations in NiMo6, indicating that NiMo6 is successfully loaded on Co-MOF.

[0040] Figure 5 Shown are the XRD patterns of Co-MOF, NiMo6 and Co-MOF / NiMo6 composites. In the XRD pattern, the diffraction peaks at 11°, 26°, 29° and 32° match the diffraction peaks of NiMo6, and the diffraction peaks at 16°, 18°, 22.5° and 27° belong to Co-MOF, which confirms the successful preparation of the Co-MOF / NiMo6 composite.

[0041] Figure 6 The graph shows the ammonia production rate and Faraday efficiency of the Co-MOF / NiMo6 composite material in a neutral electrolyte (0.1 mol / L NaNO3 and 0.1 mol / L Na2SO4) at room temperature and pressure at a voltage of -0.5 to -0.9 V for 1 hour. The average ammonia production efficiency of the Co-MOF / NiMo6 composite material is 11.14 mg h at a potential of -0.8 V vs. RHE. -1 mgcat. -1 , and the Faraday efficiency is 98.2% with good electrocatalytic nitrate reduction to ammonia production activity. Therefore, the preparation of the composite material in the present invention improves the electrocatalytic efficiency, and the Co-MOF / NiMo6 composite material can be used as an efficient electrocatalytic nitrate reduction catalyst.

[0042] Figure 7 The electrochemical linear sweep voltammogram of the Co-MOF / NiMo6 composite material in the presence or absence of nitrate is shown. As shown in the figure, in the voltage range of -0.4V vs.RHE to -1.4V vs.RHE, the reduction current density of the Co-MOF / NiMo6 composite material in the electrolyte containing nitrate ions is significantly higher than the reduction current density of the electrolyte without nitrate ions, indicating that the Co-MOF / NiMo6 composite material has a certain electrocatalytic nitrate reduction ability.

[0043] In summary, the present invention is a preparation and application of an Anderson-type polyacid-modified Co-MOF composite material, and successfully prepared a composite material Co-MOF / NiMo6 with a nanoflower shape, which increases the specific surface area of ​​the material and enhances the efficiency of electrocatalytic nitrate reduction to produce ammonia. The synthesized Co-MOF / NiMo6 composite material has great potential in electrocatalytic nitrate reduction to produce ammonia.

Claims

1. A preparation process of Anderson-type polyacid-modified Co-MOF nanoflower-shaped electrocatalyst, characterized by: (1) Preparation of NiMo6 polyacid: (NH 4)6 7O 24 ·4H2O (5-8g) is dissolved in 80mL of deionized water to obtain a solution and heated to boiling. Dissolve NiSO4·5H2O (0.6-1g) in 20mL of deionized water and pour into the above boiling solution. In order to obtain purer crystals, the solution is recrystallized. The mixed solution is allowed to stand and cool. During the cooling process, NiMo6 crystals will gradually crystallize out of the solution. After the crystallization process is basically completed, use a Buchner funnel with a suction filtration bottle to separate the crystals from the mother liquor by suction filtration to finally obtain light blue crystals; (2) Preparation of metal organic framework Co-MOF: Dissolve Co(NO3)2·6H2O (0.3-0.4 g) in 100 mL of deionized methanol, and dissolve 2-methylimidazole (0.3-0.4 g) in 100 mL of deionized methanol. Then mix the above solutions, first put the mixed solution into an ultrasonic cleaner for 20 minutes, then stir for 30 minutes, and let it stand for 24 hours. Collect the purple product by centrifugation, then wash with deionized methanol, and vacuum dry at 60°C for 12-14 hours to obtain Co-MOF; (3) Preparation of composite materials: Co-MOF (0.2-0.5 g) was dissolved in 170 mL of deionized methanol, and NiMo6 (0.2-0.5 g) was dissolved in 70 mL of deionized water. The solutions were mixed, and then polyvinyl pyrrolidone (0.01-0.05 g) was added. The mixture was stirred for 8 hours and then allowed to stand for 24 hours. The product was collected by centrifugation, and then washed with methanol and water for 2-3 times, respectively, and dried under vacuum at 60°C for 12-14 hours to obtain Co-MOF / NiMo6.

2. The cooling temperature in step (1) of claim 1 is in the range of 22 to 25°C.

3. The volume of the deionized methanol according to step (2) of claim 1 is 100 mL.

4. According to step (2) of claim 1, the masses of Co(NO3)2·6H2O and 2-methylimidazole are 3-4g and 4-5g respectively.

5. The mass of polyvinylpyrrolidone (PVP) according to step (3) of claim 1 is 0.01-0.05g.

6. According to step (2) and step (3) of claim 1, the drying temperature is 60° C. and the drying time is 720-840 minutes.

7. The drying process according to step (3) of claim 1 should be carried out under vacuum conditions.

Citation Information

Patent Citations

  • Pyridyl Anderson type polyacid crystal and preparation and application of composite material of pyridyl Anderson type polyacid crystal

    CN117143160A

  • Self-assembled low-crystallization nano flower-shaped polyoxometallate catalyst as well as preparation method and application thereof

    CN119287444A

  • MOF-derived nitrogen cobalt heterogeneous nanobox electrocatalyst, preparation method therefor, and use thereof

    WO2024234835A1